Development Of Caring Approach Of Normal Chilbirth To Increase Midwife Competence - Umami, Riza; Prijatni, Ida (Jurnal Pendidikan Kesehatan, 2020)
Midwives in assisting childbirth use the Normal Childbirth Care Standard so that labor is correct and safe, but the fact is the maternal and infant mortality rates are still high. Caring is a form of care given by midwives to clients based on caring, sincere, gentle and loving and considers that the client is our own family. Caring behavior is very necessary because caring is the core of midwife performance to meet client welfare. This study aims to develop Normal Childbirth Care by integrating caring elements. The type of research used is Research and Development with the aim of developing Caring Approach based Normal Childbirth Care in order to improve midwife competence. The design of this study is quasi experimental. Sampling used a purposive sampling of 45 midwife respondents who had PMB in the Jember Regency. The instrument uses a questionnaire. Data analysis used Wilcoxon Signed Rank Test with significance p equal 0.05. Results of this study are all standards need to be integrated caring, by integrating caring in the steps of Normal Childbirth Care in increasing the competence of midwives can reduce the incidence of death in mothers and infants so that client welfare and satisfaction are met.